2020
DOI: 10.1002/cssc.202001155
|View full text |Cite
|
Sign up to set email alerts
|

From Electronic Waste to Suzuki−Miyaura Cross‐Coupling Reaction in Water: Direct Valuation of Recycled Palladium in Catalysis

Abstract: From electronic waste to Pd-catalyzed reaction! The straightforward valuation of palladium recovered from electronic waste is reported here. Following a classical leaching stage, palladium is selectively extracted from a complex aqueous mixture of metallic cations into an organic phase. Afterwards, the judicious choice of a surfactant enables stabilization of palladium during back extraction cycles, and the direct preparation of an aqueous micellar solution, which can be employed in a model SuzukiÀ Miyaura cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In a recent report, Bourgeois et al described a process for recovering palladium as a catalytic micellar solution from multi-layer ceramic capacitors (MLCC) recovered from WEEE. The group employed their previously reported recovery process, which involved selective dissolution of silver and palladium from the gold present using a heated (50 • C) 3M nitric acid solution [98]. After leaching, palladium was selectively extracted using one of two organic extractants tested (L1 and L2), followed by back-extraction with a surfactant based on tris-(hydroxymethyl)acrylamide (S1) (Figure 9).…”
Section: Direct Application Of Recovered Palladium In Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report, Bourgeois et al described a process for recovering palladium as a catalytic micellar solution from multi-layer ceramic capacitors (MLCC) recovered from WEEE. The group employed their previously reported recovery process, which involved selective dissolution of silver and palladium from the gold present using a heated (50 • C) 3M nitric acid solution [98]. After leaching, palladium was selectively extracted using one of two organic extractants tested (L1 and L2), followed by back-extraction with a surfactant based on tris-(hydroxymethyl)acrylamide (S1) (Figure 9).…”
Section: Direct Application Of Recovered Palladium In Catalysismentioning
confidence: 99%
“…Micellar back-extraction of recovered palladium [98]. Reproduced with permission [98] The group then explored the catalytic activity of their micellar palladium solution.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Metal-rich PCBs are excellent raw materials for the preparation of various metal nanoparticles (NPs): Ag NPs on C, Cu 2 O NPs, Cu NPs, , Cu–Sn NPs, and PbO NPs . Although a variety of materials can be obtained, only a few have been shown to possess interesting catalytic properties and are typically limited to the degradation of organic dyes. , Notably, Bourgeois and co-workers reported a method for selective palladium extraction from electronic waste, which was further stabilized by surfactants in the aqueous phase . It has been demonstrated that these Pd solutions can serve as a convenient medium for Suzuki–Miyaura coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Notably, Bourgeois and co-workers reported a method for selective palladium extraction from electronic waste, which was further stabilized by surfactants in the aqueous phase. 18 It has been demonstrated that these Pd solutions can serve as a convenient medium for Suzuki−Miyaura coupling reactions.…”
Section: ■ Introductionmentioning
confidence: 99%